Societal costs and health related quality of life in adult atopic dermatitis - Zsuzsanna Beretzky; Kamilla Koszorú; Fanni Rencz; Krisztina Hajdu; Júlia Borza; Katalin Bodai; Xu Feifei; Andrea Szegedi; Miklós Sárdy; Valentin Brodszky (BMC, 2023)
Abstract Background Cost-of-illness studies are widely used for healthcare decision-making in chronic conditions. Our aim was to assess the cost-of-illness of adult atopic dermatitis (AD) from the societal perspective in Hungary. Methods We conducted a multicentre, cross-sectional questionnaire survey between February 2018 and January 2021. Data was collected from consecutive AD patients aged ≥ 18 years and their physicians at dermatology departments in Hungary. We calculated direct and indirect costs, including costs for treatments, outpatient visits, hospital admissions, informal care, travel costs and productivity loss. To assess indirect costs, the Work Productivity and Activity Impairment (WPAI) questionnaire was used to collect data, and costs were estimated with the human capital approach. Generalized linear model was used to analyse predictors of total, direct and indirect costs. Results Altogether 218 patients completed the survey (57.8% female) with an average age of 31.3 (SD = 11.7). Patients' average Dermatology Life Quality Index (DLQI) score was 13.5 (SD = 8.5). According to Eczema Area and Severity Index (EASI) score, 2.3% (n = 5), 21.2% (n = 46), 54.4% (n = 118) and 22.1% (n = 48) had clear, mild, moderate, and severe AD, respectively. We found that the average total, direct medical, direct non-medical and indirect annual costs per patients were €4,331, €1,136, €747, and €2450, respectively, with absenteeism and presenteeism being the main cost drivers, accounting for 24% and 29% of the total cost of AD. A one-year longer disease duration led to, on average, 1.6%, and 4.2% increase in total and direct non-medical costs, respectively. Patients with worse health-related quality of life (higher DLQI score) had significantly higher total, direct medical, direct non-medical costs, and indirect costs. Conclusions Our results indicate a substantial economic burden of AD from a societal perspective, mainly driven by productivity losses.